2017
DOI: 10.1021/acs.jctc.7b00623
|View full text |Cite
|
Sign up to set email alerts
|

Use of Crystal Structure Informatics for Defining the Conformational Space Needed for Predicting Crystal Structures of Pharmaceutical Molecules

Abstract: Determining the range of conformations that a flexible pharmaceutical-like molecule could plausibly adopt in a crystal structure is a key to successful crystal structure prediction (CSP) studies. We aim to use conformational information from the crystal structures in the Cambridge Structural Database (CSD) to facilitate this task. The conformations produced by the CSD Conformer Generator are reduced in number by considering the underlying rotamer distributions, an analysis of changes in molecular shape, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Such conformer generation is recommended subsequent to creating an initial threedimensional geometry if desired. [36,38,39,40,41,42,43,44,45]…”
Section: Resultsmentioning
confidence: 99%
“…Such conformer generation is recommended subsequent to creating an initial threedimensional geometry if desired. [36,38,39,40,41,42,43,44,45]…”
Section: Resultsmentioning
confidence: 99%
“…Such conformer generation is recommended subsequent to creating an initial threedimensional geometry if desired. [36,38,39,40,41,42,43,44,45]…”
Section: Resultsmentioning
confidence: 99%
“…Some discrepancies between the predicted and experimental geometries occurred for the ligand: Macromolecule complexes in unusual conformational space, rare rotamer examples, uncertain bond types, and some other cases, nevertheless, theoretical configuration space represents well experimental data [265,266] or configurations obtained by the Molecular Operating Environment's Low Mode Molecular Dynamics module [267]. It was demonstrated that the CSD-Conformer Generator combined with ab initio [268] or DFTB3-D3 [269] calculations can be used for crystal structure prediction of some flexible pharmaceuticals. Such combination reproduced well the molecular geometry and crystal parameters, although did not provide sufficiently accurate energy ranking.…”
Section: Csd-conformer Generatormentioning
confidence: 97%